The Future of Banking: The Role of Information Technology: Challenges and Opportunities for Banks in the Digital Era (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The article examines the impact of information technology (IT) on the banks and on the banking industry as a whole. Over the years, the economic foundation of banking has not changed much. However, as IT-driven banking interactions are extremely cost-effective, the emphasis on transaction banking has been increasing with time. But, the industry should not sacrifice their relationship banking concept. Banks should understand the changing consumer preferences and drive different aspects of IT to make these new demands feasible through relationship banking model. For this, banks may need to re-engineer their relationship banking concepts. Remodeling of banking activities is also required as FinTech companies have been seizing market shares of the traditional banks. Government interference and various regulations are providing some relief to the banking industry for the time being.